Development of a biosensor for detecting biphenyl/polychlorinated biphenyls (PCBs) on the basis of bph-genes of bacteria-destructors isolated from anthropogenic soils of the Western Urals - Shumkova, E.S.; Shumkov, M.S.; Korsakova, E.S.; Egorova, D.O.; Shestakova, E.A.; Plotnikova, E.G. (Perm Federal Research Centre Journal, 2017)
A specific genetic construct was created, which is actually a modified plasmid pET19b into which bph-operon ( bphA4, bphA123B ) genes of Rhodococcus ruber strain P25 were introduced under the control of a T7-lac -promoter. Intentionally induced synthesis of these protein molecules leads to the appearance of functional enzymes of "upper" biphenyl/PCBs degradation pathway in E. coli cytoplasm that provides the transformation of the pollutants to the clc -operon-inducing chemical compounds (clc-operon is responsible for chlorocatechol destruction). The Clc -genes of R. opacus 1CP strain were placed into the E. coli chromosome as the basis of clcRA::rfp reporter fusion. The latter is the biosensor detection unit, which responds to the PCB degradation products and similar organic compounds.In the course of the biosensor construction the whole genome sequencing of R. ruber strain P25 - an active destructor of biphenyl/PCBs - was carried out. Totally 3,677 genes were annotated (69.6%). The draft genome sequence was deposited in GenBank under NZ_LDUF00000000.1 number. A gene cluster of biphenyl/chlorobiphenyl degradation was identified. The bph -operon structure of the P25 strain appeared to be different in comparison with that of known bacteria- destructors of biphenyl/PCBs: bhRorf2orf1A4DCA1A2A3B . The transcription of orf1 and orf2 loci is performed in the opposite direction with bphR and bphA4DCA1A2A3B .